ETYMOLOGY AND ITS SUBJECT MATTER (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This insightful article delves into the fascinating realm of etymology, the study of word origins, and the subject matter it encompasses. The author provides a historical backdrop, tracing the roots of etymology from ancient civilizations to the Renaissance, highlighting key figures who contributed to its development. The subject matter of etymology is comprehensively explored, touching on word origins, cultural insights, language evolution, semantic shifts, and cross-cultural connections. The article emphasizes how etymology serves as a linguistic time machine, unraveling the intricate histories of words and offering a profound understanding of language as a reflection of human civilization. It adeptly illustrates how studying the origins and evolution of words not only enriches our vocabulary but also unveils the cultural, historical, and social contexts embedded in language. Overall, the article presents a compelling narrative that captivates readers, inviting them on a linguistic adventure that transcends the boundaries of words to reveal the interconnected tapestry of human communication.